Matilda - Dahl, Roald (London Puffin Books, 2016)
Matilda's parents have called her some terrible things, but the truth is she's a genius and they're the stupid ones. Underestimating Matilda proves to be a big mistake as they, along with her spiteful headmistress, Miss Trunchbull, discover when Matilda uses her very special power to get the better of them
Keywords: Fiction